Recirculation as the form of destination of the Concentrate originated from the Treatment of leachate in landfills by Membrane Processes - Lippi, Marcelo; Gaudie Ley, Michelle Bellas Romariz; Mendez, Gabriel de Pinna; Felix Cardoso Junior, Ricardo Abraches (Ciência e Natura, 2021)
The different methodologies of leachate treatment are widely debated in the literature, promoting a great discussion among the scientific and academic community on the most efficient and propitious methods. Membrane treatment processes, especially Reverse Osmosis (RO), stand out as the best solution. The RO has pollutant removal rates higher than 99%, with operational cost and complexity competitive with other technologies. Its main disadvantage is the concentrated residue generated in the process that covers about 30% of the volume of leachate entering the system. Its recirculation in the body of the landfill arises as an alternative of low destination cost. Its effectiveness is directly related to the method of recirculation along the geological, climatological, technical and operational conditions of the landfills. Although already widespread, the treatment or destination of the concentrate requires a greater technological assertion. Further research is needed on the recirculation methods of the concentrate and its medium and long-term effects on leachate, settlement and landfills after care period. It is important to make a comparative analysis of landfills with similar characteristics, one with and another without recirculation of the concentrate. Alternatives to treat the concentrate are also of great interest whether they are economically viable in real scale.